Mechanisms of Listening Effort in Individuals with Hearing Loss - Zahra Iran Pour Mobarakeh; Marzieh Amiri; Elham Tavanai; Vida Rahimi (Journal of Modern Rehabilitation)
Introduction: Listening effort refers to the cognitive resources required to understand speech, particularly in challenging environments. Individuals with hearing loss experience increased listening effort due to auditory deficits, affecting their communication and cognitive load. Understanding the mechanisms underlying listening efforts is essential for developing effective hearing interventions. This study aims to explore the mechanisms underlying listening efforts in individuals with hearing impairments. Materials and Methods: A narrative review was conducted using specific keywords in Google Scholar (as a search engine) and the research databases Web of Science, Scopus and PubMed. Relevant articles were selected based on their alignment with the focus on the mechanisms of listening effort in individuals with hearing loss. Results: Hearing loss triggers compensatory cognitive strategies, engaging the prefrontal regions and working memory to process degraded auditory signals. Neural adaptations, including cross-modal plasticity and reliance on top-down processing, further elevate mental workload. Degraded temporal processing and attentional demands in noisy environments exacerbate effort, often leading to fatigue. Conclusion: Understanding these mechanisms informs interventions, such as adaptive hearing technologies, cognitive training to optimize resource allocation and personalized communication strategies. Integrating neurophysiological insights into clinical practice can reduce cognitive fatigue and enhance communication outcomes.